SISTEM INFORMASI PENGOLAHAN DATA PADA TOKO USAHA BARU - Windy Adriana; Louis, Ahmad; Adriana, Windy; -, Emillia (LP2M Universitas Nurdin Hamzah, 2023)
Toko Usaha Baru is the subject of research where the management of sales data and stock of incoming and outgoing goods at this Toko Usaha Baru still uses a manual recording system into a large agenda book. The items that have been recorded a 6re then calculated using a calculator to find out the total consumer purchases. Furthermore, for processing monthly sales and stock data reports, the shop owner must recap it from the existing large agenda book notes. After being analyzed and evaluated as a whole, it is necessary to develop an information system for the activities of Toko Usaha Baru which is later expected to be able to expand marketing, speed up the process and produce information more quickly, precisely and accurately in accordance with the wishes of the owner. The goal is to make it easier for Toko Usaha Baru owner to manage goods and financial data, make it easier for shop owners to manage item data and make it easier for shop owners to control debts and receivables